Effectiveness of Using Wordwall Digital Learning Media in Improving Students' Understanding of History Learning - Usmaedi, Usmaedi; Ayu Ningtyas, Tiara; Sampurna, Iman; Jumyadi, Jumyadi (Jurnal Ilmiah WUNY, 2026)
Background: The background of this research is based on students' low interest and understanding of history lessons due to the dominant conventional learning methods. Objectives: To involve two 11th-grade classes at SMA Negeri 1 Cimarga, namely the experimental class using Wordwall and the control class using the lecture method. Method: The research method used is quantitative with a quasi-experimental design, involving two 11th-grade classes at SMA Negeri 1 Cimarga, namely the experimental class using Wordwall and the control class using the lecture method. Result: The research results showed a significant difference between student learning outcomes in the experimental class and the control class, with a significance value of 0.006 < 0.05. Furthermore, the average N-Gain value in the experimental class of 57.08 is included in the quite effective category, while the control class only reached 33.74 (less effective). These findings indicate that Wordwall is effective in improving students' understanding of history learning. Conclusion: Therefore, interactive digital media such as Wordwall are recommended for use in history learning to create a more engaging and meaningful learning atmosphere.